Alpha-lipoic acid (ALA) in diabetes mellitus-induced erectile dysfunction (DMED): preliminary efficacy from an interim analysis - Abu Kassim, Madihah; Haydar Ali Tajuddin, Amalina; Ahmad Kasim, Ahmad Zulhazwan (Faculty of Medicine, UKM, 2025)
Introduction: Erectile dysfunction (ED) is a common complication of type 2 diabetes mellitus (T2DM) related to endothelial dysfunction, neuropathy and oxidative stress. Alpha-lipoic acid (ALA), a potent antioxidant, has been shown to be beneficial in diabetic neuropathy and adjunctive ED therapy, but its role as monotherapy in diabetes mellitus-induced erectile dysfunction (DMED) remains unclear.